Exceptional Circumstances as a Limitation on the Principle of Legality A Comparative Study - AL-Kalbani, Hamad (Journal of Ecohumanism, 2025)
This research examines the state of emergency as a restriction on the principle of legality, through a comparative study of the French and Egyptian legal systems, with reference to the legal framework in the Sultanate of Oman. The study begins by establishing the principle of legality as a cornerstone of the rule of law, requiring all state authorities to be subject to legal rules. It then explores the exception permitted by exceptional circumstances, which arises when the state faces grave dangers that cannot be addressed through ordinary legal provisions. The research outlines the doctrinal and Islamic jurisprudential foundations of this theory, the position of administrative courts regarding its Practice, and the distinction between exceptional circumstances and acts of sovereignty. It further highlights the safeguards that prevent the misuse of exceptional powers, foremost among them judicial oversight, and sets out the criteria that balance security requirements with the protection of rights and freedoms. The study concludes with a set of recommendations to strengthen the legislative and regulatory framework governing exceptional circumstances in Oman, in line with constitutional principles and international obligations.